Morphological variability of Hister shanghaicus Marseul, 1862 (Coleoptera, Histeridae) - Ji-Huan Zheng; Tomáš Lackner (Biodiversity Data Journal)
Dorsal elytral striae serve as key diagnostic characters in the taxonomy and species identification of Histeridae beetles. The variation of dorsal elytral striae in Hister shanghaicus Marseul, 1862 is documented herein, based on specimens collected from Gutian Nature Reserve (Guangdong Province) and Jiulianshan Nature Reserve (Jiangxi Province), southern China. The distribution of H. shanghaicus is also updated.